2016
DOI: 10.1021/acs.jctc.5b00952
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of the Alanine Dipeptide in Water–Ethanol Binary Mixtures

Abstract: Experimental work developed in the last years has evidenced the capacity of alcohols and polyalcohols to modify the energy landscape of peptides and proteins. However, the mechanism underlying this effect is not clear. Taking as a model system the alanine dipeptide (AD) we perform a QM/MM study in water, ethanol, and a 40-60% in volume water-ethanol mixture. The AD molecule was described at the MP2/aug-cc-pVDZ level. In polar solution, only αR and PPII conformers contribute in an appreciable way to the conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 82 publications
1
9
0
Order By: Relevance
“…This term, DV, can be evaluated by applying the harmonic oscillator and rigid rotor approximations to the vibrational and rotational modes of the solute in solution, and it needs the information provided by the Hessian matrix, something that makes its calculation difficult in solution systems. In a previous study 72 it was found that the contribution of this term to the conformational equilibrium of a small dipeptide was lower than 0.1 eV. In pCE À we find a similar value.…”
Section: Methods and Computational Detailssupporting
confidence: 80%
See 2 more Smart Citations
“…This term, DV, can be evaluated by applying the harmonic oscillator and rigid rotor approximations to the vibrational and rotational modes of the solute in solution, and it needs the information provided by the Hessian matrix, something that makes its calculation difficult in solution systems. In a previous study 72 it was found that the contribution of this term to the conformational equilibrium of a small dipeptide was lower than 0.1 eV. In pCE À we find a similar value.…”
Section: Methods and Computational Detailssupporting
confidence: 80%
“…Oscillator strengths were calculated using the RASSI algorithm implemented in Molcas-7.4. 65 Solvent effects were introduced using the averaged solvent electrostatic potential from the molecular dynamics data (ASEP/MD) method [69][70][71][72][73][74] developed in our laboratory. The method permits combining the quantum-mechanical description of the solute with the microscopic description of the environment.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radial distribution function (RDF), denoted g(r), is a measure of the probability of finding two atoms at a distance r from each other. This parameter is recurrent in MD trajectory analysis, including in other systems [49][50][51][52]. Its mathematical expression can be written as follows: is the total volume of the system.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…More recently, in a QM/MM study devoted to understand the conformational behavior of the alanine dipeptide in ethanol-water mixtures it is shown that in contrast to the results in water, the αR conformation exhibits lower energy than the PII conformation in ethanol [29].…”
Section: Introductionmentioning
confidence: 99%